Knowledge and perceptions towards organic farming: a case of pineapple farmers in central Uganda - S. Nalubwama; F. Bagamba; F. Kabi; Z. Nampijja; M. Kiggundu; K. Kamatara; N. Kwikiriza; D. Nampanzira; A. Nalunga; V. Lutwama; J. Nasaka (Discover Agriculture)
Abstract This study examined the knowledge and perceptions as well as factors that influence the knowledge and perceptions of pineapple farmers towards organic farming in Uganda. Through multi-stage sampling procedures, purposive and random techniques were applied at different stages to select participants from both Luwero and Kayunga districts in central Uganda. Data was collected using a semi-structured questionnaire. A composite index for knowledge and perceptions was computed for each respondent and subjected to descriptive statistics while the censored Tobit regression model was used to determine factors that influenced farmers’ knowledge and perceptions of organic farming. Results showed that both organic and non-organic farmers had a high level of knowledge and favorable perceptions towards organic farming with no significant difference. Perceived environmental and economic benefits of organic farming did not significantly differ (p > 0.05) among organic and non-organic farmers. However, mean scores for perceived health and nutritional (4.30 vs. 3.94) benefits, and access to markets (4.10 vs. 3.89) differed significantly (p < 0.05) between organic and non-organic farmers. There was a positive and significant relationship between knowledge and perception of organic farming among non-organic farmers while for organic farmers, a significant and negative relationship was observed. Factors that significantly influenced farmers’ knowledge were information sources and farmers’ experiences. Farmer perceptions were influenced by education, information sources, group membership and extension services. Therefore, to enhance the adoption and growth of organic pineapple production in Uganda, policymakers and promoters should consider these factors when designing policy documents and sustainability strategies for the development of organic agriculture.